The Inclusive Behavioral Immune System - Shakhar, Keren (Frontiers in Psychology, 2019)
Although living in social groups offers many advantages, it comes at a cost of increased transmissible disease. The behavioral immune system (BIS) is thought to have evolved as a first line of defense against such infections. It acts by minimizing the contact of yet uninfected hosts with potential pathogens. The BIS has been observed in a wide range of animals including insects, amphibians and mammals, but most research has focused on humans where the BIS is guided by complex cognitive and emotional processing. When researchers discuss the evolutionary origin of the BIS, they assess how it raises individual fitness. What would happen though if we shift our attention to the evolutionary unit of selection – the gene? Success would be measured as the change in the gene’s prevalence in the entire population, and additional behaviors would come to our attention – those that benefit relatives, i.e., behaviors that raise inclusive fitness. One widely-recognized example of the inclusive BIS is social immunity, which is prevalent among eusocial organisms such as bees and ants. Their colonies engage in a collaborative protective behavior such as grooming and the removal of infected members from the nest. Another example may be sickness behavior, which includes the behavioral, cognitive and emotional symptoms that accompany infection, such as fatigue, and loss of appetite and social interest. My colleague and I recently suggested that sickness behavior has evolved because it reduces the direct and indirect contact between an infected host and its healthy kin – improving inclusive fitness. These additional behaviors are not carried out by the healthy individuals, but rather by whole communities in the first case, and by already infected individuals in the second. Since they step beyond the classical definition of BIS, it may be useful to broaden the term to the inclusive behavioral immune system.